Islamic Business Strategy of Hotel Matahari Jambi in Increasing the Number of Visitors - Shofiyah Shofiyah; Salmia Salmia; Muhamad Saleh; Mohd Haramen (CV Edujavare Publishing, 2026)
This study examines the Islamic business strategy implemented by Hotel Matahari Jambi in increasing the number of visitors through the application of Islamic ethical values in hotel operations. The findings reveal that the hotel consistently applies Islamic principles by enforcing operational policies such as verifying guest identities and permitting only legally married couples to stay together, reflecting its commitment to morality, discipline, and social responsibility. Although the hotel has not obtained formal halal certification, these practices successfully create a safe, comfortable, and family-friendly environment that positively influences customer perceptions, particularly among Muslim visitors seeking accommodation aligned with religious values. The implementation of Islamic ethics also strengthens customer trust, emotional comfort, and the hotel’s positive reputation, which contributes to customer loyalty and repeat visits. In addition, the Islamic-oriented operational system serves as a differentiation strategy within the competitive hospitality industry by positioning the hotel as an ethically responsible and morally consistent business entity. Therefore, the experience of Hotel Matahari Jambi demonstrates that the practical implementation of Islamic business values can become an effective strategy for improving customer satisfaction, strengthening competitive advantage, and increasing the number of visitors even without official halal certification.